2016
DOI: 10.1039/c6gc02642g
|View full text |Cite
|
Sign up to set email alerts
|

A combination of natural deep eutectic solvents and microflow technology: a sustainable innovation for the tandem synthesis of 3-aminohexahydrocoumarins

Abstract: A combination of natural deep eutectic solvents with microfluidic technology presents a powerful and attractive technique in the modern synthesis of fine chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Most of the studies demonstrated the high antibacterial or antifungal properties of DES and NADES, which can be an advantage for certain chemical processes, especially in the biotech industry. ,, The toxicity may be used as an advantage in understanding cellular metabolic pathways as well as a potential anticancer agent. , These solvents have low vapor pressures, good thermal stabilities, and broad applications, which make them extremely attractive as replacements to traditional organic solvents. However, concerns arise particularly for soil and water contamination at the point of disposal.…”
Section: Deep Eutectic Solvents (Des)mentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies demonstrated the high antibacterial or antifungal properties of DES and NADES, which can be an advantage for certain chemical processes, especially in the biotech industry. ,, The toxicity may be used as an advantage in understanding cellular metabolic pathways as well as a potential anticancer agent. , These solvents have low vapor pressures, good thermal stabilities, and broad applications, which make them extremely attractive as replacements to traditional organic solvents. However, concerns arise particularly for soil and water contamination at the point of disposal.…”
Section: Deep Eutectic Solvents (Des)mentioning
confidence: 99%
“…214,238,244 The toxicity may be used as an advantage in understanding cellular metabolic pathways as well as a potential anticancer agent. 243,245 These solvents have low vapor pressures, good thermal stabilities, and broad applica- tions, which make them extremely attractive as replacements to traditional organic solvents. However, concerns arise particularly for soil and water contamination at the point of disposal.…”
Section: Toxicity Of Desmentioning
confidence: 99%
“…Despite the role as therapeutic agents, the available synthetic methods require toxic solvents or metal catalysts, with adverse effects on the environment. A new tandem approach to prepare the 3-aminohexahydroxcoumarins directly from aryl aldehydes, ippuric acid, acetic anhydride, and 1,3-dicarbonyl compounds, with ChCl/urea as a biorenewable solvent was developed by Zamani and Khosropour [ 64 ]. After preliminary studies in the bath, the reactions were conducted in a continuous micro-flow reactor, including two tubing glass (Q1 for aryl aldehydes, hippuric acid, and acetic anhydride, and Q2 for 1,3-dicarbonyl compounds) giving faster and quicker results.…”
Section: Choline-based Des As Solvents/catalysts In Pharmaceutical Synthesismentioning
confidence: 99%
“…Numbering‐up the PEEK reactors was attempted, but inconsistent results were obtained in the different reactors. Other flow procedures were reported for accessing coumarin scaffolds such has 132 , …”
Section: Continuous Flow Preparation Of Active Pharmaceuticalsmentioning
confidence: 99%